A Research on the Concept and Attitude of Jyotiba Phule’s Views on Human Rights of Backward Classes/ Lower Castes: The Role of Jyotiba Phule in Socio-Religious Reform and Advocacy for Justice (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The process of getting regarding socio religious reform in nineteenth century wasn't as easy. Community reformers had made huge work for religious and social change in Indian society throughout this particular period. Phule played a remarkable job in this specific place. To be able to treat the troubles of gender as well as caste oppression, he contributed with a constructive suggestion. Throughout the life of his, Jyotiba Phule fought for the emancipation of the downtrodden individuals as well as the struggle which he released at a era ended just as he died on 28th November 1890. He was an innovator in areas that are numerous and among the contemporaries of his he sticks out as one that have never hesitated in the mission of his for Justice and truth.